Twelve Good Men and True : The Criminal Trial Jury in England, 1200-1800 - Cockburn, J. S. (Book collections on Project MUSE., 2014)
Twelve Good Men and True brings together some of the most ambitious and innovative work yet undertaken on the history of an English legal institution. These eleven essays examine the composition of the criminal trial jury in England, the behavior of those who sat as jurors, and popular and official attitudes toward the institution of jury trial from its almost accidental emergence in the early thirteenth century until 1800. The essays have important implications for three problems central to the history of criminal justice administration in England: the way in which the medieval jury.